Effects of tai chi qigong on psychosocial well-being among hidden elderly, using elderly neighborhood volunteer approach: a pilot randomized controlled trial - Chan, Aileen WK (Clin Interv Aging, 2017)
PURPOSE: To test the feasibility and preliminary effectiveness of a tai chi qigong program with the assistance of elderly neighborhood volunteers in strengthening social networks and enhancing the psychosocial well-being of hidden elderly. PATIENTS AND METHODS: “Hidden elderly” is a term used to describe older adults who are socially isolated and refuse social participation. This pilot randomized controlled trial recruited 48 older adults aged 60 or above who did not engage in any social activity. They were randomized into tai chi qigong (n=24) and standard care control (n=24) groups. The former group underwent a three-month program of two 60-minute sessions each week, with the socially active volunteers paired up with them during practice. Standard care included regular home visits by social workers. Primary outcomes were assessed by means of the Lubben social network and De Jong Gieveld loneliness scales, and by a revised social support questionnaire. Secondary outcomes were covered by a mental health inventory and the Rosenberg self-esteem scale, and quality of life by using the 12-Item Short Form Health Survey. Data was collected at baseline, and at three and six months thereafter. RESULTS: The generalized estimating equations model revealed general improvement in outcomes among participants on the tai chi qigong program. In particular, participants reported a significantly greater improvement on the loneliness scale (B=−1.32, 95% confidence interval [CI] −2.54 to −0.11, P=0.033) and the satisfaction component of the social support questionnaire (B=3.43, 95% CI 0.10–6.76, P=0.044) than the control group. CONCLUSION: The pilot study confirmed that tai chi qigong with elderly neighborhood volunteers is a safe and feasible social intervention for hidden elderly. Its potential benefits in improving social and psychological health suggest the need for a full-scale randomized controlled trial to reveal its empirical effects.